Implementasi Metode Game Based Learning pada Materi Pecahan Sederhana untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Negeri Pohsangit Lor 1 - Fifi; Anandita Salsabila; Abdul Malik Gusairi; Sullamuz Zainul Muttakin; Nur Wiji Sholikin (PT Cendekia Education Center, 2026)
This study aimed to determine the effect of implementing the Game-Based Learning method on students’ learning outcomes in the topic of Simple Fractions for fourth-grade elementary school students. The background of this study was based on students’ low understanding of fraction concepts, as indicated by classroom observations and initial test scores that were below the minimum mastery criteria. To address this issue, the Game Based Learning method was applied by integrating game elements into the learning process, thereby enhancing students’ motivation, participation, and comprehension. This research employed a quantitative approach using a One-Group Pretest–Posttest Design. The participants consisted of 25 fourth-grade students. The research instruments were pretest and posttest questions used to measure students’ learning outcomes before and after the implementation of the learning method. The data were analyzed using IBM SPSS Statistics through normality testing and the Paired Sample t-Test. The results showed that the mean pretest score of 58.00 increased to 79.52 in the posttest. Furthermore, the Paired Sample t-Test revealed a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Game-Based Learning method had a significant positive effect on improving students’ learning outcomes in the topic of Simple Fractions among fourth-grade elementary school students.